“I am borrowing ya mixing?" An Analysis of English-Hindi Code Mixing in Facebook - Bali, Kalika; Sharma, Jatin; Choudhury, Monojit; Vyas, Yogarshi (Proceedings of the First Workshop on Computational Approaches to Code Switching, 2014)
Code-Mixing is a frequently observed phenomenon in social media content generated by multi-lingual users. The processing of such data for linguistic analysis as well as computational modelling is challenging due to the linguistic complexity resulting from the nature of the mixing as well as the presence of non-standard variations in spellings and grammar, and transliteration. Our analysis shows the extent of Code-Mixing in English-Hindi data. The classification of Code-Mixed words based on frequency and linguistic typology underline the fact that while there are easily identifiable cases of borrowing and mixing at the two ends, a large majority of the words form a continuum in the middle, emphasizing the need to handle these at different levels for automatic processing of the data.